Pendekatan Trauma-Informed dalam Pekerjaan Sosial: Memulihkan Korban Trauma dan Meningkatkan Resiliensi - Pasaribu, Lenni Melina (Jurnal Sains Sosio Humaniora, 2024)
This study investigates the implementation of trauma-informed care (TIC) within social work, focusing on the experiences and challenges faced by practitioners and students. A qualitative research design was employed, utilizing Google Form questionnaires to gather data on participants' understanding of trauma, their experiences with TIC, and the obstacles encountered in its application. The findings reveal a significant gap in training and understanding of TIC among practitioners, alongside various systemic challenges that impede effective implementation. Despite these challenges, the study highlights the potential benefits of TIC, including improved practitioner awareness and enhanced client support. Recommendations for developing targeted training programs and policy adjustments are proposed to facilitate the integration of TIC into social work practice, ultimately aiming to better serve trauma victims and foster resilience.